Improving detection efficiency in a cryogenic environment - implications for DESIREE. (July 2015) - Anderson, E K; Rosén, S; Reinhed, P; Alexander, J D; Sullivan, N; Tremsin, A; Gorelikov, D; Zettergren, H; Cederquist, H; Schmidt, H T
Synopsis: The high electrical resistance of a microchannel plate at cryogenic temperatures presents a severe limitation on the detection count rate at low temperatures. We are currently investigating the detector properties of a novel atomic layer deposition activated MCP developed by Gorelikov et al [1]. This is of particular interest to us as MCPs are used for particle detection at the cryogenic DESIREE facility at Stockholm University.